Laparoscopic Supracervical Hysterectomy and Laparoscopic Total Hysterectomy in Patients with Very Large Uteri: a Retrospective Single-Center Experience at a Major University Hospital - Schöller, Dorit (Geburtshilfe Frauenheilkd, 2017)
Objective The main objectives of our study were to demonstrate that laparoscopic supracervical hysterectomy (LSH) or total laparoscopic hysterectomy (TLH) can be performed safely even in patients with a uterine weight ≥ 500 g, to analyze the rate of conversions to laparotomy due to uterine size and to estimate the incidence and type of intraoperative and long-term postoperative complications. Study Design Retrospective open, single-center, comparative interventional study of LSH and TLH. Results The present study comprised a total of 138 patients that underwent laparoscopic hysterectomy with a uterine weight ≥ 500 g; 109 patients (79.0 %) underwent LSH and 29 patients (21.0 %) underwent TLH. Median uterine weight across the entire cohort was 602 g, with the largest uterus weighing 1860 g. A total of 24 cases (17.4 %) among the 138 hysterectomies were converted to a laparotomy due to lack of adequate intraabdominal space and size of the uterus. Mean uterine weight of the patients in the LSH group that underwent conversion was 883 g (SD 380 g, n = 13) and 757 g (SD 371 g, n = 11) in the TLH group. The rate of conversion to laparotomy due to the uterine weight was significantly lower in the LSH group (11.9 %) compared to the TLH group (37.9 %) (p = 0.002). Intraoperative complications requiring laparotomy for other reasons but uterine size occurred in 6 patients of the study cohort (6/138; 4.3 %). Long-term postoperative complications occurred in 2 patients (2/138, 1.4 %), both patients from LSH group had to be re-operated on due to adhesions. Conclusions Our study adds further insight in the limited data set of laparoscopic hysterectomy for increased uterine weight and shows that LSH and TLH are safe and feasible even in patients with very large uteri (≥ 500 g).